Body between Dualisms: speeches and experiences on the body during theatrical formation - del Mármol (Universidad Nacional de La Plata, La Plata – Argentina), Mariana (Revista Brasileira de Estudos da Presença, 2022)
This article examines the emphasis which, in certain contexts in the formation of actors and the practice of acting in the city of La Plata, Argentina, is placed on the centrality of the body in theatre.The purpose of this article is to examine how the centrality of body in theatre is highlighted in certain contexts of learning and practice of acting in the city of La Plata. In order to do this, the body is placed in a network of relationships through which corporality is confronted and, at the same time, articulated with other terms representing that other territory of the human realm in face of which the value of corporality is highlighted: those relationshipsestablished between body and text or body and word; those established between body and mind or body and thinking; and those that put the body in relation to a number of references we have gathered under the concept of subjectivity.